DEVELOPMENT OF A WEB-BASED NEW STUDENT ADMISSION INFORMATION SYSTEM - Akmal Hidayat; A. Sriwana Army; Ahmad Abdillah Fathur Rachman; Muhammad Nur Ilham; Muhammad Ihsan Arif (Jurnal Media Elektrik, 2024)
Admission of new students is a routine activity carried out by schools every new school year. This activity aims to advance the school so that in its implementation a selection is needed. This selection is carried out in order to achieve a target of achieving the quality of prospective students. In this new student admission, a committee is needed to facilitate the activity. Currently, not many schools in Indonesia have implemented an online admission system. The purpose of this research is to design a web-based new student admission information system "SIPSB" and facilitate the registration of prospective new students to be more efficient. In designing this new student admission information system, the Object Orientred Analysis and Design (OOAD) method and the waterfall model are used. The use of the waterfall model in this study makes it easier for researchers to design information systems because there are several stages in system development, namely requirements analysis, system design, implementation, system testing, and maintenance. The results of this study show that the new student admission information system "SIPSB" is able to manage the web-based new student admission process more efficiently.